О реализации валентности при субстантивированных словах(On Valency Realization in the Syntax Frame of Substantivized Words) - Lönngren, Lennart (Poljarnyj vestnik, 2000)
Amongst the syntactic attributes of a substantivized adjective or participle some are normal in the sense that they semantically modify the noun, whereas others are arguments inherited, so to speak, from the corre- sponding adjective or verb. One of these arguments is expressed by the substantivized word itself, but there may also be one, or even two, addi- tional arguments expressed by case forms, prepositional phrases, verbs in the infinitive, or adverbs.
Keywords: Russian‚ language; valency; nominalization